(untitled) (Comparative & International Education Series, 2022)
This study aims to explore the impact of an Internationalization at Home program prior to the stay abroad on the extent to which students develop intercultural competences during their year abroad. Being capable of behaving appropriately and effectively in a complex global context is an invaluable transferrable skill that enhances graduates’ employability. We found that the year abroad had a significant impact on the extent to which students developed their intercultural competences, but only when they had taken an IaH program prior to their year abroad. Our research, therefore, suggests that an IaH program operates as a moderator that affects the impact of the year abroad on the development of graduates’ intercultural competence development. How to cite in APA: Puymbroeck, C. V., Gerretsen, C., & Shinnick, J. (2022). Understanding the impact of international student mobility on students’ employability through internationalization at home curriculum. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 95-108). STAR Scholars. [order hardcopy ]